2019
DOI: 10.3390/su11205824
|View full text |Cite
|
Sign up to set email alerts
|

Improving Self-Efficacy Towards Inclusion in In-Service Physical Education Teachers: A Comparison between Insular and Peninsular Regions in Spain

Abstract: Physical education teachers play a significant role in educating students with special education needs, but they often feel frustrated and unprepared to achieve a successful inclusion process. The lack of inadequate training has proven to have an unfavorable effect on educators’ perceived competence, confidence, and attitudes when working in inclusive settings with children with disabilities. This study evaluates the effect of a training program implemented with in-service physical educators from two different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 25 publications
2
14
0
8
Order By: Relevance
“…A possible explanation for why participants reported the highest level of self-efficacy toward the inclusion of students with intellectual disabilities might be because they may be aware or had watched the Saudi national team for athletes with intellectual disabilities win the International Sports Federation for Persons with Intellectual Disability (INAS) World Football Championship four times (2006, 2010, 2014, and 2018). Indeed, Reina et al [2] concluded that watching para-sports and having positive interactions with para-athletes are necessary to improve teachers' self-efficacy towards inclusive education in PE classes and foster sustainable development in education.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A possible explanation for why participants reported the highest level of self-efficacy toward the inclusion of students with intellectual disabilities might be because they may be aware or had watched the Saudi national team for athletes with intellectual disabilities win the International Sports Federation for Persons with Intellectual Disability (INAS) World Football Championship four times (2006, 2010, 2014, and 2018). Indeed, Reina et al [2] concluded that watching para-sports and having positive interactions with para-athletes are necessary to improve teachers' self-efficacy towards inclusive education in PE classes and foster sustainable development in education.…”
Section: Discussionmentioning
confidence: 99%
“…The United Nations Sustainable Development Goal Four (SDG-4) aims to ensure inclusive and equitable quality education for all [1]. It is focused on providing high-quality education and ensuring that all students (including those with disabilities) are provided with highly motivated, well-supported, and well-qualified teachers [2]. Qualified and well-prepared teachers are vital in implementing a successful inclusive education [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…En este sentido, los docentes juegan un papel decisivo para hacer realidad la educación inclusiva (Jerlinder, Danermark & Gill, 2010). Así las cosas, se observa que, en los últimos años, una parte vital para implementar una inclusión exitosa son las actitudes y la autoeficacia del docente (Reina, Ferriz & Roldán, 2019, Reina, Santana, Montesdeoca & Roldán, 2019. Comprender las perspectivas de los docentes sobre la inclusión es crucial en la investigación educativa (Abdi, 2017), más aún quizás el factor más importante para una inclusión exitosa en EF es la actitud y la competencia percibida de los docentes de EF (Block et al, 2016) porque las actitudes son un determinante importante del comportamiento de los docentes (Cyran, Kudlacek, Block, Malinowska-Lipien & Zyznawska, 2017).…”
Section: Actitudes Del Profesorado De Educación Física Hacia La Incluunclassified
“…Selfefficacy is a very important factor for the decision of persons with disabilities to engage in sports (Dixon-Ibarra & Driver, 2013), and on the other hand, it is assumed that participation in sports will increase the self-efficacy of persons with disabilities (Moss et al, 2017). Also, the self-efficacy of teachers in working with students with disabilities is extremely important (Block, Taliaferro, Harris & Krause, 2010) and increases with participation in specialized programs (Tindall, Culhane, & Foley, 2016;Reina, Santana, Montesdeoca, & Roldan, 2019;Foley, Santarossa, Tindall, & Lieberman, 2020).…”
Section: Introductionmentioning
confidence: 99%